A cross-linguistic study of the acquisition of clitic and pronoun production - Belletti, Adriana; Costa, João; Friedmann, Naama; Gavarró, Anna; Grohmann, Kleanthes K.; Guasti, Maria Teresa; Tuller, Laurice; Lobo, Maria; Anđelković, Darinka; Argemí, Núria; Avram, Larisa; Berends, Sanne; et al. (My University, 2015)
This study develops a single elicitation method to test the acquisition of third-person pronominal objects in 5-year-olds for 16 languages. This methodology allows us to compare the acquisition of pronominals in languages that lack object clitics (“pronoun languages”) with languages that employ clitics in the relevant context (“clitic languages”), thus establishing a robust cross-linguistic baseline in the domain of clitic and pronoun production for 5-year-olds. High rates of pronominal production are found in our results, indicating that children have the relevant pragmatic knowledge required to select a pronominal in the discourse setting involved in the experiment as well as the relevant morphosyntactic knowledge involved in the production of pronominals. It is legitimate to conclude from our data that a child who at age 5 is not able to produce any or few pronominals is a child at risk for language impairment. In this way, pronominal production can be taken as a developmental marker, provided that one takes into account certain crosslinguistic differences discussed in the article.
Keywords: Test; Pronoun languages; Clitic language